NGOs' Advocacy in the 2015 Refugee Crisis: A Study of Agenda Building in the Digital Age. (April 2018) - Yang, Aimei; Saffer, Adam
In the 2015 European refugee crisis, nonprofit and nongovernmental organizations (NGOs) offered help and actively advocated for millions of refugees. The current study aims to understand what communication strategies are most effective for NGOs to influence media coverage and the public's social media conversations about refugees. We found that agenda building on traditional media and in social media conversations require different strategies. Specifically, although providing information subsidies could powerfully influence traditional media coverage, its effect waned in the context of social media conversations. In contrast, NGOs' hyperlink network positions emerged as the one of the influential factors for NGOs' prominence in social media conversations. Moreover, stakeholder-initiated engagement could influence agenda building both in traditional media coverage and social media conversations. Finally, organizational resources and characteristics are important factors as well. Theoretical and practical implications are discussed.